THE INFLUENCE OF ORGANIZATIONAL CULTURE, WORK MOTIVATION, AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE - Silvia Ersa Rahmadania; Anik Herminingsih (Dinasti Publisher, 2021)
This study aims to determine and analyze the influence of organizational culture , motivation to work , and work discipline t erhadap performance of employees at PT TJB . This research was conducted on 80 respondents who are permanent employees, data collection techniques using questionnaires. The research design used is causality . Data processing is done by analysis of Partial Least Square ( Smart -PLS) version 3.0. The results of the study show that organizational culture dominated by the type of hierarchy, the most dominant work motivation is about the need for achievement or achievement and work discipline is about obedience to work rules. The results of hypothesis testing prove that organizational culture, work motivation and work discipline have a positive and significant effect on employee performance at PT TJB